2015
DOI: 10.1111/mec.13158
|View full text |Cite
|
Sign up to set email alerts
|

Genetically distinct populations of northern shrimp, Pandalus borealis, in the North Atlantic: adaptation to different temperatures as an isolation factor

Abstract: The large-scale population genetic structure of northern shrimp, Pandalus borealis, was investigated over the species' range in the North Atlantic, identifying multiple genetically distinct groups. Genetic divergence among sample localities varied among 10 microsatellite loci (range: FST = -0.0002 to 0.0475) with a highly significant average (FST = 0.0149; P < 0.0001). In contrast, little or no genetic differences were observed among temporal replicates from the same localities (FST = 0.0004; P = 0.33). Spatia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
77
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(88 citation statements)
references
References 76 publications
10
77
1
Order By: Relevance
“…We clearly identified a “source” role for northern populations (SFA 4–6) in our study area and a primarily “sink” role for southern populations (SFA 6 and 7) within a stream‐like connectivity system driven by the Labrador Current, confirming that northern shrimp stocks behave as a metapopulation (e.g., Jorde et al., ; Kritzer & Sale, ). Moreover, we found poor connectivity between eastern SFAs (SFA 4–7) and the Gulf of St. Lawrence (SFA 8) and southwest of Newfoundland (SFA 9).…”
Section: Discussionsupporting
confidence: 80%
“…We clearly identified a “source” role for northern populations (SFA 4–6) in our study area and a primarily “sink” role for southern populations (SFA 6 and 7) within a stream‐like connectivity system driven by the Labrador Current, confirming that northern shrimp stocks behave as a metapopulation (e.g., Jorde et al., ; Kritzer & Sale, ). Moreover, we found poor connectivity between eastern SFAs (SFA 4–7) and the Gulf of St. Lawrence (SFA 8) and southwest of Newfoundland (SFA 9).…”
Section: Discussionsupporting
confidence: 80%
“…The impact of abiotic features in promoting genetic differentiation has been investigated recently by Jorde et al (2015) who correlated the spatial genetic patterns in the northern shrimp Pandalus borealis throughout its North Atlantic distribution zone with geographic distances, patterns of larval drift obtained through oceanographic modelling, and temperature differences, within a multiple linear regression framework. The authors found that bottom temperature differences explained the most multiple genetically distinct groups of the investigated species, indicating a major role played by local adaptation to temperature conditions in promoting evolutionary diversification and speciation in the marine environment.…”
Section: Discussionmentioning
confidence: 99%
“…While some studies found a congruence between the biophysical and genetic approaches (Buonomo et al, ; Hernawan et al, ; Schiavina, Marino, Zane, & Melià, ; Schunter et al, ; Sjöqvist, Godhe, Jonsson, Sundqvist, & Kremp, ), other investigations demonstrated discrepancies (Galindo et al, ). Furthermore, a congruence may be detected only at larger spatial scales but not at smaller scales (Foster et al, ; Johansson et al, ) or vice versa (Jorde et al, ).…”
Section: Introductionmentioning
confidence: 99%